Novel biallelic SZT2 mutations in 3 cases of early‐onset epileptic encephalopathy. Issue 2 (18th September 2017) - Tsuchida, N.; Nakashima, M.; Miyauchi, A.; Yoshitomi, S.; Kimizu, T.; Ganesan, V.; Teik, K.W.; Ch'ng, G.‐S.; Kato, M.; Mizuguchi, T.; Takata, A.; Miyatake, S.; et al.
Abstract : The seizure threshold 2 ( SZT2 ) gene encodes a large, highly conserved protein that is associated with epileptogenesis. In mice, Szt2 is abundantly expressed in the central nervous system. Recently, biallelic SZT2 mutations were found in 7 patients (from 5 families) presenting with epileptic encephalopathy with dysmorphic features and/or non‐syndromic intellectual disabilities. In this study, we identified by whole‐exome sequencing compound heterozygous SZT2 mutations in 3 patients with early‐onset epileptic encephalopathies. Six novel SZT2 mutations were found, including 3 truncating, 1 splice site and 2 missense mutations. The splice‐site mutation resulted in skipping of exon 20 and was associated with a premature stop codon. All individuals presented with seizures, severe developmental delay and intellectual disabilities with high variability. Brain MRIs revealed a characteristic thick and short corpus callosum or a persistent cavum septum pellucidum in each of the 2 cases. Interestingly, in the third case, born to consanguineous parents, had unexpected compound heterozygous missense mutations. She showed microcephaly despite the other case and previous ones presenting with macrocephaly, suggesting that SZT2 mutations might affect head size. Abstract : Pedigrees of families (upper) and schematic presentation of recessive mutations in SZT2 (lower). Eight previously reported mutations and the 6 mutations found in this study are shown above and below SZT2, respectively.